Barcode-Based Flascard Making Training at TK Plus Tunas Rimba - Melani Indah Pertiwi (Experimental Student Experiences, 2024)
Technological educational media can provide an overview in developing more interesting learning methods. Current technological developments can be used as innovative solutions in the development of educational media to attract students' interest in the learning process. This service aims to enable educators to utilize technology in making learning media. This service was carried out at TK Plus Tunas Rimba with 9 teachers participating. This service activity consists of several stages, namely preparation and targeting of the target group and implementation. The results of the activities that have been carried out are (1) the teacher knows the benefits and functions of barcord-based flashcard media for early childhood. (2) the teacher knows how to make barcord-based flashcard media using the Canva and Vocaroo applications. (3) the teacher knows how to use barcode-based flashcard media by scanning barcodes in the Google Lens application.